PERAN KARITAKUR DALAM MENINGKATKAN KEMAMPUAN BERPIKIR DAN MEMBENTUK OPINI PUBLIK DIKALANGAN PARA SISWA - Gunanti, Dewa Ayu Made Dwi (Widyadari: Jurnal Pendidikan, 2018)
This study aims to determine the ability of observation on caricature to improve the ability to write opinion class XII IPS 1 SMA Negeri 1 Selemadeg; (2) to know the steps taken by observation on caricature in improving the writing skill of class XII IPS 1 SMA Negeri 1 Selemadeg; (3) to find out the student's response about observing caricatures to improve the ability to write opinions. The research method used in this research is classroom action research. The results of this study were There are 11 students (32.35%) answered hesitant to the second statement that is about the observation of the caricature can facilitate students in writing opinions. Eighteen students (52.94%) answered agree while 4 students (11.76%) answered strongly that observation on caricature can make it easier to write an opinion. The majority of students, 24 students (70.59%) answered agreeably to the third question that observation of caricatures can give students a topic in opinion writing. In addition, there are also 7 students (20.59%) answered hesitantly, 2 students (5.88%) answered strongly agree to the statement. Against the fourth statement of observation on caricatures can assist students in making arguments in favor of statements, there are 17 students (50%) answered agreeing by observing caricatures can assist students in making arguments in favor of statements.